(untitled) (International Conference on Scientific Research in Natural and Social Sciences, 2025)
Oral mucositis continues to be one of the most frequent and distressing complications arising from chemotherapy, exerting a profound negative impact on the overall well-being and quality of life of cancer patients. The onset of mucositis frequently compels clinicians to delay, reduce, or discontinue antineoplastic treatment regimens, thereby undermining therapeutic efficacy and adversely influencing clinical outcomes and disease prognosis. In addition to its clinical implications, this condition imposes a substantial financial burden, significantly elevating the cost of patient care and contributing to prolonged durations of hospital stays.Considering both the clinical severity and economic impact of chemotherapy-induced oral mucositis, there is an urgent and growing demand for the development and implementation of more effective, affordable, and scientifically validated treatment and prevention methods. Existing therapeutic modalities are often insufficient, involving multi-step procedures, expensive medications, or resource-intensive interventions, which may limit their widespread use in routine oncology practice. As a result, it is essential to explore innovative, patient-friendly, and evidence-based strategies that can improve outcomes while reducing the strain on healthcare systems.